1986
DOI: 10.1068/p150235
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Recognition with Interchanged Facial Features

Abstract: Any attempt to unravel the mechanism underlying the process of human face recognition must begin with experiments that explore human sensitivity to differences between a perceived image and an original memory trace. A set of three consecutive experiments are reported that were collectively designed to measure the relative importance of different facial features. The method involved the use of image-processing equipment to interchange cardinal features among frontally viewed target faces. Observers were require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
96
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 19 publications
13
96
0
4
Order By: Relevance
“…It was shown by O'Donnell and Bruce (2001) that people are highly sensitive to changes in the eye region when they are familiarized with. Other results confirm the significance of the upper half of face (Haig 1986) and eyebrows. In experiment described by Sadr et al (2003), subjects recognized the faces of celebrities with removed eyebrows significantly worse than the faces without eyes (with the mean difference of 9.5 %).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…It was shown by O'Donnell and Bruce (2001) that people are highly sensitive to changes in the eye region when they are familiarized with. Other results confirm the significance of the upper half of face (Haig 1986) and eyebrows. In experiment described by Sadr et al (2003), subjects recognized the faces of celebrities with removed eyebrows significantly worse than the faces without eyes (with the mean difference of 9.5 %).…”
Section: Introductionsupporting
confidence: 74%
“…Changes of foreheads, eyes and mouths caused the lowest error rates made by subjects. Similar results were presented in Haig (1986) and Matthews (1978) where the observers indicated that eye/eyebrows followed by mouth and then nose were the most dominant regions as the recognition features (taking into account internal features only). It was shown by O'Donnell and Bruce (2001) that people are highly sensitive to changes in the eye region when they are familiarized with.…”
Section: Introductionsupporting
confidence: 69%
“…By measuring reaction-time changes caused by the omission or substitution of facial features in schematic linedrawn faces, Fraser et al (1) reproduced previous findings by Haig (2) with photographic images that certain features are more important to face recognition than others. In particular, a feature hierarchy was observed with the head outline as the most significant, followed by the eyes, mouth and then nose.…”
Section: Introductionmentioning
confidence: 77%
“…Adult humans can recognize and remember faces from the eyes alone and experiments assessing the relative importance of different features for face recognition have consistently shown the dominance of the eye/eyebrow combination [43][44][45][46][47]. This may reflect several factors.…”
Section: Discussionmentioning
confidence: 99%